2019
DOI: 10.47291/efi.v65i1.597
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Diversity in the Boardroom Improve Firm Performance? Evidence from Indonesia

Abstract: This study investigates board gender diversity in Indonesia’s listed firms and its effect on firm performance from 2011–2016. After addressing the endogeneity of diversity, the results in this paper show that the proportion of female in the boardroom marginally improve firm performance. Firms with two or more female in the boardroom have a stronger impact on firm performance than firms with one female in the boardroom, consistent with the critical mass effect. Finally, certain sectors will gain more benefits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
(15 reference statements)
1
12
0
5
Order By: Relevance
“…Meanwhile, studies in the Indonesian context are limited. Pasaribu et al (2019) found that gender diversity is positively related to Indonesian firms’ financial performance. In contrast, Darmadi (2013) pointed out that having more women on the top executive management affects adversely on firms’ financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, studies in the Indonesian context are limited. Pasaribu et al (2019) found that gender diversity is positively related to Indonesian firms’ financial performance. In contrast, Darmadi (2013) pointed out that having more women on the top executive management affects adversely on firms’ financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study argued the negative influence of female boards on all listed companies' market performance in Indonesia. Passaribu et al (2019) mentioned that female directors' composition in the 100 biggest Indonesian listed companies remained the same from 2012 to 2014 at 11%-12%. The study found that even though females on board can JAEE 13,2 positively impact firm profit, women's participation on the board is still low.…”
Section: Working Capital Management and Firm Performancementioning
confidence: 99%
“…The study argued the negative influence of female boards on all listed companies' market performance in Indonesia. Passaribu et al . (2019) mentioned that female directors' composition in the 100 biggest Indonesian listed companies remained the same from 2012 to 2014 at 11%–12%.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Several board diversity studies in Indonesia found that increasing gender diversity in the boardroom has a beneficial effect on firm performance. Firms with two or more women in the boardroom have a stronger impact on firm performance than firms with only one woman in the boardroom (Pasaribu et al , 2019; Syamsudin et al , 2017). The presence of women in the governance function can reduce the agency problem in the company and reduce the practice of earnings manipulation because of the relevance of ethical and moral issues(Razak and Helmy, 2020).…”
Section: Introductionmentioning
confidence: 99%